2022
DOI: 10.3390/en15155556
|View full text |Cite
|
Sign up to set email alerts
|

Bus Voltage Control of Photovoltaic Grid Connected Inverter Based on Adaptive Linear Active Disturbance Rejection

Abstract: According to the traditional voltage and current double closed-loop control mode, the inverter management strategy for photovoltaic grid connection has insufficient anti-interference ability and slow response. This paper proposes a control strategy that applies adaptive-linear active disturbance rejection control (A−LADRC) to the outer loop control to achieve the purpose of anti-interference. The control strategy uses the linear extended state observer (LESO) to evaluate external interference caused by the cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 34 publications
(44 reference statements)
0
1
0
Order By: Relevance
“…Aiming at the weak anti-interference ability of a photovoltaic grid connected inverter management scheme, an improved LADRC controller was proposed by Refs. [19,20], which optimizes the parameters by observing and estimating the total interference by linear extended state observer (LESO), compensating the interference by the PD controller and adding adaption. The results showed that the improved method has better rapidity and robustness.…”
Section: A Literature Reviewmentioning
confidence: 99%
“…Aiming at the weak anti-interference ability of a photovoltaic grid connected inverter management scheme, an improved LADRC controller was proposed by Refs. [19,20], which optimizes the parameters by observing and estimating the total interference by linear extended state observer (LESO), compensating the interference by the PD controller and adding adaption. The results showed that the improved method has better rapidity and robustness.…”
Section: A Literature Reviewmentioning
confidence: 99%
“…In [23], the LADRC controller was applied to the control scheme of a high-speed train, so that the train can achieve speed tracking control accurately and rapidly, and the impact caused by external interference is suppressed. In [24], in order to keep the DC bus voltage of the inverter stable during operation, LADRC is applied to the inverter control strategy to complete the control of the inverter bridge. This method enhances the response speed of the system and effectively responds to the interference caused by changes in external conditions.…”
Section: Introductionmentioning
confidence: 99%